So old, so young : a novel - Ginder, Grant (Scout Press, 2026)
"Six Friends. Five Parties. Twenty Years... How did we get So Old, So Young? From Grant Ginder, the bestselling author of The People We Hate at the Wedding, comes a novel of impending millennial middleage that is part love story, part tragic comedy. Five parties over the course of two decades bring six college friends together, exploring the ways we can run from and cling to our friends in love, life,and death. For Marco and Mia, Sasha and Theo, Richie and Adam, theone constant in life after college together has been change. New jobs. New cities. New spouses. New children. Through it all, one thingthey thought would always stay the same is their friendship. But time has a way of breaking even the strongest bonds and testing what we thought we knew. From East Village apartment parties and disastrous destination weddings to fortieth birthdays and suburban backyard barbecues, Grant Ginder's resonant, funny, and deeply moving novel isa story about the growing pains of the millennial generation, and acelebration of how love can shift, stumble, and grow into something bigger than we ever could have imagined"--